Prevalence of bromide in groundwater in selected regions in South Africa - Lucht, HL; Casey, NH (Water SA, 2019)
Many regions across South Africa are dependent on groundwater as the only water source for livestock watering and domestic use. This paper presents an analysis of 350 water samples from collated data of 5 reports published between 2001 and 2016 that show the vast range of 0–132.68 mg/L bromide (Br−) present in South African groundwater. It further highlights that Br− may be a greater toxicity risk factor to livestock production and human health as an endocrine disrupting chemical (EDC) and through accumulation in organs than previously considered. Further validation is required of the physiological effects of Br− for inclusion in water quality guidelines (WQG). Attention is drawn to the importance of site-specific water quality (WQ) monitoring and identification of vulnerable populations to enable adequate risk assessment and implementation of mitigating strategies to lower exposure risk in a specific area.